JEM-EUSO observational technique and exposure - Bertaina, M. (2015)
Designed as the first mission to explore the ultra-high energy universe from space, JEM-EUSO observes the Earth’s atmosphere at night to record the ultraviolet tracks generated by the extensive air showers. We present the expected geometrical aperture and annual exposure in the nadir and tilt modes for ultra-high energy cosmic rays observation as a function of the altitude of the International Space Station.